ORGANIZATIONAL CULTURE, SHARED TASK, AND JOB SATISFACTION AMONG BUSINESS EDUCATORS IN EDO STATE - CHUKWUEMEKE, HELEN EDOWAYE; OWENVBIUGIE, ROBINSON OSARUMWENSE (Sokoto Educational Review, 2022)
This study focused on organizational culture and shared tasks as they influenced the job satisfaction of business educators in tertiary educational institutions in Edo State. A survey design was adopted and data were collected with the aid of a questionnaire. The population of the study consisted of fifty-six business educators from six tertiary institutions in Edo State. The entire population of fifty-six business education teachers in the tertiary institution was used for the study. The instrument was face validated. Its reliability was measured using the split-half method, Pearson Product Moment Correlation Coefficient(r) and Brown's correction formula were used to measure the level of consistency and 0.89 was obtained. Data collected were analyzed using simple percentages, mean, standard deviation and t-tests. Results revealed that organizational culture and shared tasks influenced job satisfaction while gender, years of service, age and marital status did not. Some recommendations were made in this regard which includes that there should be knowledge of the organization's core values helps to prevent the internal conflict that leads to dissatisfaction, also good and healthy organizational culture should exist in tertiary institutions to prevent the internal conflict that leads to dissatisfaction. Finally, business educators believed that when they have a work environment that is helpful, considerate and cooperative as well as a team-oriented organizational culture this will lead to job satisfaction.